Survival and inhibition of Clostridium sporogenes P.A.3679 in nitrite-cured tocino - Catbagan, Katherine P.; Azanza, Ma. Patricia V. (1999., 1999)
The survival and growth of artificially-inoculated viable spores of Clostridium sporogenes (PA 3679) was studied in refrigerated nitrite-cured tocino. The natural aerobic and anaerobic bacterial flora were also established in the stored commodity. Changes in the physico-chemical and sensory attributes were correlated with the observed changes in the microbial profiles. The effects of cooking on the survival of the artificially-inoculated organism and in the natural flora were determined. Artificial inoculation of the tocino with Cl. sporogenes significantly increased (α = 0.05) the aerobic mesophilic, total anaerobic mesophilic and viable anaerobic spore counts but not the aerobic psychrophilic counts. Refrigerated storage of tocino, resulting to an internal temperature in the range of 7.0 to 8.7°C, caused a significant decrease in all the monitored microbial counts. Only aerobic psychrophilic counts significantly decreased in inoculated samples. Softening and souring of both uninoculated control and inoculated samples were observed after 12 d of storage. These were attributed to the fermentative actions of the aerobic and anaerobic mesophiles in the sample. The bright red cured-meat color of tocino appeared to be stable with storage. Cooking of tocino samples in oil (160-165°C) for 2-3 minutes caused ≥ 92% reduction in the microbial counts of all the test bacterial groups. There might have been possible germination of Cl. sporogenes in the samples based on a significant decrease (α = 0.05) in viable anaerobic spore counts upon inoculation and the subsequent disappearance of viable spores in the stored samples. The possible growth and multiplication of the vegetative form of the inoculated organism in tocino was assumed because of the observed increase in the counts of the anaerobic mesophilic counts during the 12 d storage. There was a delay in an increase of anaerobic mesophiles due to a lag in the growth rate of the vegetative form of Cl. sporogenes. The pH, aw and internal temperature of the refrigerated tocino samples were all found to be conducive to the survival and growth of the artificially-inoculated Cl. sporogenes spores and the natural bacterial flora in the stored commodity. Assuming that the survival and multiplication patterns of Cl. botulinum in refrigerated tocino would be parallel with Cl. sporogenes, several recommendations were made as to the minimization of botulinal risks in the stored tocino. These recommendations included the depression of pH and aw of tocino through the addition of organic acids and more solutes, respectively. Thorough cooking of the commodity and a review of the local formulations with particular emphasis on the nitrite concentrations were also recommended.
Thesis (BSFT)-University of the Philippines Diliman
Keywords: Meat -- Preservation; Food -- Microbiology